MAPPING INTERNATIONAL FINANCIAL REPORTING STANDARDS CONVERGENCE ON FINANCIAL STATEMENTS (A COMPARATIVE STUDY BETWEEN UNILEVER AT UNITED KINGDOM AND INDONESIA) - Enjelina Intan Prima Dewi; Endang Kiswara (Diponegoro Journal of Accounting, 2013)
IFRS convergence came in response to the need for relevant and comparable accounting information. IFRS convergence in the EU has started since 2005. While in Indonesia have been fully adopted IFRS from 2012. By doing convergence, then the previous financial statements presented on a GAAP basis will be amended. This study aimed to answer questions such as: what does the complexity of the load of works to be done by a company that has not been fully adopted IFRS; identify the impact of the convergence of IFRS on accounting policies and information and disclosures in the notes to the financial statements of the companies; and what is the proposed mapping strategy that could assist the companies to do their convergence action.The research was conducted by the comparative method of qualitative analysis through case studies on two companies, Unilever Group in the UK and PT.Unilever Indonesia Tbk in Indonesia. The data used are secondary data from the companies’ annual financial statements in 2011. Analysis of the financial statements of the company made toward the 12 IFRS, 26 IAS and 26 PSAK.Refer to 12 IFRS, 26 IAS ,and 26 PSAK analyzed the results showed that the load of works of company (PT. Unilever Indonesia Tbk) that will be full convergence with IFRS is quite complex because of the number of standards to be adopted and the nature of the regulatory principle-based so it requires more judgment and disclosures in the notes to the financial statements. Disclosures made in the notes to the financial statements are more detail because of the use of judgment in financial reporting. The impact of IFRS convergence is significantly seen in the concept of measuring the elements of financial statements in which the fair value is more widely used. Disclosure of items in financial statements is more detail due to the using of judgment in financial reporting. Understanding and evaluating toward new adopted standards and developing a robust accounting policies and procedures followed by gradual adoption of standards is one of mapping strategy that could assist the companies in doing their convergence action.